Cancer and psychiatry - Thekkumpurath, P; Sharpe, M (2009)
Cancer is common, affecting one in three people in UK during their lifetime. Psychological factors are relevant in the prevention of cancer and also in how people respond to cancer and its treatment. This article provides an overview of the area, referred to as psycho-oncology, from a psychiatric clinician's point of view. The most common psychiatric problem in the management of patients with cancer is that of emotional disorders. These are very common but still remain under-diagnosed and under-treated. Systematic screening using self-report measures can improve their detection, and is recommended in cancer centres. However, the effective delivery of treatments for these conditions to the large number of patients with cancer remains a challenge. Initial evaluation of a new approach in which cancer nurses deliver treatment for depression under psychiatric supervision has shown promising initial results. © 2009 Elsevier Ltd. All rights reserved.